2021
DOI: 10.2478/mgr-2021-0015
|View full text |Cite
|
Sign up to set email alerts
|

From the agricultural station to a luxury village? Changing and ambiguous everyday practices in the suburb of Vinnytsia (Ukraine)

Abstract: The study of everyday practices, self-identities and perceptions seems to be a promising approach to understand the suburban spaces as not only static containers but socially constructed, dynamic and ambiguous entities. Our case study is represented by the suburban village of Ahronomichne, located in the peri-urban area of the second-order Ukrainian city of Vinnytsia. The research methods included survey of residents (67 long-term residents and 59 newcomers), observations of the everyday activities of the resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Residents in host communities usually tend to be open to discussions about the benefits of the project; however, the lack of opportunity to have a voice in the decision-making process exacerbates their personal feeling that they were not treated well or justly [52]. There is no doubt that inadequacies in communication strategies towards the public [53] and the prevalence of a one-way-only information flows about the project are responsible for unnecessary tensions within communities [14]. We confirmed that this problem occurs even in apparently problem-free communities hosting AD plants.…”
Section: Discussionmentioning
confidence: 99%
“…Residents in host communities usually tend to be open to discussions about the benefits of the project; however, the lack of opportunity to have a voice in the decision-making process exacerbates their personal feeling that they were not treated well or justly [52]. There is no doubt that inadequacies in communication strategies towards the public [53] and the prevalence of a one-way-only information flows about the project are responsible for unnecessary tensions within communities [14]. We confirmed that this problem occurs even in apparently problem-free communities hosting AD plants.…”
Section: Discussionmentioning
confidence: 99%
“…Restitution and privatization after 1991, and especially the substantial cuts to agricultural subsidies after 1993, led to dramatic changes in agricultural production and the whole rural way of life (Bezemer 2000; Chodkowska‐Miszczuk, Kulla, and Novotny 2019; Gnatiuk, Mezentsev, and Provotar 2021; Pénzes and Demeter 2021; Van der Horst et al 2018; Veznik and Bartosova 2004). These changes deepened the process of abandonment of rural landscapes, not only in the former Czechoslovakia but also throughout the whole of Central and Eastern Europe (Dzenovska 2020).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…The migration of men and women as separate sciences was identified in the 1980s in Western Europe (Schwabe & Weziak-Bialowolska, 2022). Female migration affects employment quality and way of life (Gnatiuk et al, 2021); in essence, women's autonomy. Migration processes are interconnected with changes in information data, mental work transformations, and the development of cultural characteristics (Malchrzak et al 2022).…”
Section: Introductionmentioning
confidence: 99%